A educação linguística no curso de Letras: contribuições para o ensino de Língua Portuguesa - Segredo, Ligiane Cristina (2011)
Considering the need for teachers with the aim of educating in a better quality, the current research has as its subject Formation of Portuguese Language Teacher and it is mainly focused on Language Education. Thus, adopts as object of studies a Language Course in a private university in the inner of São Paulo for an exploratory qualitative research, a methodology which best support the most wanted objectives. To investigate whether the Portuguese language teacher are getting a consistent educational preparation suitable with the precepts of Language Education, firstly, institutional documents were analyzed, as the proposal of the Language Course, the document was written by teachers which recommend the separation of Portuguese and English undergraduate students and the political pedagogic project on the Language Course Portuguese. They offer data to analyze the profile of the professional graduated in Language, as, upon conclusion the course, is eligible to teach at the elementary school. Afterward, were analyzed information obtained through an interview with the coordinator of the Language Course and also a questionnaire answered by recent grads teachers of the course in the study, which allows knowing the universe that constitutes the course in question. The result of data analysis reveal the Language Course, after separate the undergraduate students, has provided a consistent training to Portuguese teacher, by making available on the program studies of oral, reading, writing, lexicon and grammar through disciplines that concern in focus on both aspect, analytical perspective and practice